1990
DOI: 10.1002/crat.2170251214
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and fundamental physical properties of Sn2SbS2I3 and Pb2SbS2I3 compounds

Abstract: The oriented ingots of isostructural compounds Sn,SbSZ13 and Pb,SbS,13 were prepared using a modified Bridgman method. The lattice parameters of the prepared orthorhombic compounds have been determined by a X-ray powder diffraction analysis. From the spectral response of the photoconductivity the following values for the forbidden zone of the prepared sulfides-iodides were found: E,(Sn,SbS,13) 1.5 eV, E,(Pb,SbS,I,) = 2.0 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 1 publication
4
37
0
Order By: Relevance
“…6). Notably, this electronic structure allows the explanation of the reported 'anomalous' trend in band gap energies within the A 2 SbS 2 I 3 (A = Sn, Pb) isostructure family, for which Starosta et al 12 found a gap 0.5 eV larger for the Pb-based compound. While band gaps of conventional semiconductors tend to decrease upon substitution of heavier elements, due to increased orbital energies, we witness a strong contradiction to this trend in this material class.…”
Section: The Presence Of This Previously-hidden Polar Distortion Inmentioning
confidence: 82%
See 2 more Smart Citations
“…6). Notably, this electronic structure allows the explanation of the reported 'anomalous' trend in band gap energies within the A 2 SbS 2 I 3 (A = Sn, Pb) isostructure family, for which Starosta et al 12 found a gap 0.5 eV larger for the Pb-based compound. While band gaps of conventional semiconductors tend to decrease upon substitution of heavier elements, due to increased orbital energies, we witness a strong contradiction to this trend in this material class.…”
Section: The Presence Of This Previously-hidden Polar Distortion Inmentioning
confidence: 82%
“…§ The substitution of Sn with Pb and S with Se has been demonstrated for Sn 2 SbS 2 I 3 . [10][11][12]…”
Section: Bonding Anti-bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is close to that Article previously reported (1.50 eV). 28 Sn 2 SbS 2 I 3 also showed an electron mobility of 3.22 3 10 À2 cm 2 V À1 S À1 , and the corresponding electron diffusion length was 82.8 nm (Figures S6 and S7). It should be considered that these physical values were measured with relatively impure and non-compact Sn 2 SbS 2 I 3 thin films obtained using a solution process (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Dolgikhv 27 reported the preparation of an isostructural Pb 2 SbS 2 I 3 compound and investigated its dielectric properties, especially its high-frequency permittivity. Starosta et al 28 prepared Sn 2 SbS 2 I 3 and Pb 2 SbS 2 I 3 using a modified Bridgman method, and they found that the band gaps of Sn 2 SbS 2 I 3 and Pb 2 SbS 2 I 3 are 1.5 and 2.0 eV, respectively. Although Sn 2 SbS 2 I 3 exhibits important semiconducting properties and an acceptable band gap, it has not been applied in solar cells.…”
Section: Progress and Potentialmentioning
confidence: 99%